Numerical Investigation on Effect of Multiple Winglets for Wind Turbine Applications - G., Prasad.; M., Ramesh.; K., Rajasekar. (International Journal of Engineering and Technology, 2018)
The present article is an effort to examine the potential of multiple winglets to reduce the induced drag of the aerodynamic surface. The advantages of using multiple winglets include reduction of induced drag, increased L/D and improved performance of the Wind turbine. Computational Fluid Dynamics is utilized as to approach the effects of multiple winglets with NACA 24012 airfoil section for untwisted, rectangular wing. The testing of configurations is done at Reynolds number 290,000. FLUENT solver incorporated in ANSYS used for the numerical investigation of the steady flow over the wing. A substantial improvement in lift curve slope occurs with dihedral spread of the winglets. The dihedral spread also distributes the tip vortices.Â